2010
DOI: 10.1007/s10555-010-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cells as a source of inflammatory factors for tumor progression

Abstract: Cellular senescence, which is associated with aging, is a process by which cells enter a state of permanent cell cycle arrest, therefore constituting a potent tumor suppressive mechanism. Recent studies show that, despite the beneficial effects of cellular senescence, senescent cells can also exert harmful effects on the tissue microenvironment. The most significant of these effects is the acquisition of a senescent-associated secretory phenotype (SASP), which entails a striking increase in the secretion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
438
0
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(462 citation statements)
references
References 139 publications
(180 reference statements)
9
438
0
15
Order By: Relevance
“…[41][42][43] It has been postulated that senescent stroma can contribute to disease progression by the secretion of cytokines and proteases, providing a mechanism through which the p16ink4a-positive stroma contributes to disease. 19,20,44 In summary, these data show dual facets of the RB pathway related to the pathophysiology of DCIS: disruption of RB function within the DCIS lesion, as indicated by coordinated elevation of p16ink4a and Ki-67, is associated with increased risk of recurrence; and activation of the RB-pathway, as evidenced by elevated p16ink4a in nonproliferative stroma, is an independent determinant of recurrence.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[41][42][43] It has been postulated that senescent stroma can contribute to disease progression by the secretion of cytokines and proteases, providing a mechanism through which the p16ink4a-positive stroma contributes to disease. 19,20,44 In summary, these data show dual facets of the RB pathway related to the pathophysiology of DCIS: disruption of RB function within the DCIS lesion, as indicated by coordinated elevation of p16ink4a and Ki-67, is associated with increased risk of recurrence; and activation of the RB-pathway, as evidenced by elevated p16ink4a in nonproliferative stroma, is an independent determinant of recurrence.…”
Section: Discussionmentioning
confidence: 78%
“…18 In this context, p16ink4a and the induced senescence is believed to represent a barrier to disease progression, although senescent cells have been postulated to secrete factors that could be involved in disease progression. 19,20 Although loss of p16ink4a is observed frequently in cancer and is believed to allow bypass from senescence, 21 the overexpression of p16ink4a is observed in a number of cancers wherein the RB tumor suppressor has been inactivated. [22][23][24] Thus, whereas high levels of p16ink4a could denote senescence, the elevated expression of p16ink4a in a hyperproliferative setting is believed to be indicative of loss of RB function.…”
mentioning
confidence: 99%
“…Campisi and co-workers have reported that senescent human fibroblasts stimulate pre-malignant and malignant skin and mammary human epithelial cells to proliferate in culture and to form tumours in mice, due, at least in part, to soluble factors secreted by senescent fibroblasts [87]. Subsequent studies established that senescent cells change their expression profile to a senescence-associated secretory phenotype (SASP) [88]. SASP is characterized by expression of cytokines and chemokines leading to an inflammatory response that promotes leukocyte infiltration that is immunosuppressive [89][90][91].…”
Section: The Senescence-associated Secretory Phenotype Of Cafs Promotmentioning
confidence: 99%
“…Accumulation of senescent fibroblasts in tumours may be a result of the accelerated proliferation of CAFs or a response to extrinsic genotoxic stress caused by oxidative stress and high glucose in the tumour microenvironment [88]. In addition, increased presence of senescent fibroblasts in tumours may also be part of normal ageing of the tissue where tumourigenesis occurs [52].…”
Section: The Senescence-associated Secretory Phenotype Of Cafs Promotmentioning
confidence: 99%
“…(80,81) SASP factors include several ILs, monocyte chemotactic proteins (MCPs), growth-related oncogenes (GROs), and inflammatory cytokines as granulocyte-macrophage colony stimulating factor (GM-CSF) and macrophage inflammatory proteins (MIPs), among others. (80,82,83) SASP factors can have potent effects on neighboring cells and thus can alter local and systemic tissue milieus. In the brain, it seems that the increase in p16…”
Section: Dna Damage and Nddmentioning
confidence: 99%